Réponses

2013-03-24T15:49:03+01:00

E = (3x + 2)² - (4x - 1)(3x + 2)

 

1)

E = (3x + 2)² - (4x - 1)(3x + 2)

E = 9x² + 12x + 4 - 12x² - 8x + 3x + 2

E = - 3x² + 7x + 6

 

2)

E = (3x + 2)² - (4x - 1)(3x + 2)

E = (3x + 2)[(3x + 2) - (4x - 1)]

E = (3x + 2)(3x + 2 - 4x + 1)

E = (3x + 2)(- x + 3)

 

3)

(3x + 2)(- x + 3) = 0

Je reconnais une équation produit. Or un produit est nul si l'un de ses facteurs est nul.

 

donc

3x + 2 = 0

3x + 2 - 2 = 0 - 2

3x / 3= - 2 / 3

x = - 2 / 3

 

ou

- x + 3 = 0

- x + 3 - 3 = 0- 3

- x = - 3

x = 3

-2 / 3 et 3 sont les solutions de l'équation.

 

4)

(3x + 2)(- x + 3) = (3*(- 2) + 2)(- (-2) + 3)

                           = (-6 + 2)(2 + 3)

                            = - 4 * 5

                            = - 20